Mutable environments and permeable human bodies★. (20th June 2018) - Lock, Margaret
Abstract: Geologists have declared an epochal transition to the Anthropocene, formally recognizing humans as the driving force of destructive global change; a distinction can no longer be made between human history and natural history. Certain commentators argue that Capitalocene better characterizes the situation, given that the effects of planetary decimation and global warming are not equally distributed among humans. A second conceptual change has recently taken place in which genomes are recognized as reactive to environmental stimuli both external and internal to the human body. In the post‐genomic era, genes neither initiate life nor drive human development. The science of the bourgeoning field of behavioural epigenetics is introduced, followed by illustrative examples of environmentally caused epigenetic changes that impact negatively on health. Epigeneticists routinely delimit their attention to detecting measurable changes at the molecular level. It is argued that anthropological contributions that incorporate subjective accounts of embodiment involving past and present events are crucial in order to better situate and account for biological differences and health outcomes historically, ecologically, and politically. Discussion of the microbiome provides a cautionary reminder that microbes are the ultimate driving force of health and illness. In conclusion, the Earth Optimism movement is briefly introduced, as is the concept of resilience, but alone these positive moves will not curb unremitting global warming.